Ornamental Behaviours: Mechanisms of Repetition in Urban Communities. - Lee, Lenka (Deleuze & Guattari Studies, 2025)
The interplay between urban and rural lifestyles in the modern era, influenced by globalisation, technological advancements and societal shifts, underscores a complex fusion of cultures and behaviours. This convergence reshapes communal dynamics and territorial perceptions. Drawing from Deleuze and Guattari's philosophical framework, particularly concepts of territory, deterritorialisation and reterritorialisation, this study explores the emergence of urban subcultures resembling rural communities. Through ornamental behaviour and the repetition of cultural events, urban spaces undergo a transformative process akin to ritornello, establishing distinct territories marked by creative expressions. The territories are justified and consolidated by a repeated performance of the social ornament which is a set of rules, practices and material products. All these phenomena, infused with the event (Deleuze) and moments of awe (Leddy), intertwine aesthetics and ethics, promoting community unity and well-being. This inquiry not only clarifies social phenomena but also indicates pathways for a more fulfilling societal existence.